Effectiveness of Pharmacotherapy Follow-Up for the Control of Hypertensive Patients in Community Pharmacies: EMDADER-HTA Study (2013)
ABSTRACT: The present study was designed to evaluate the effect of pharmacotherapy follow-up (PFU) on blood pressure (BP) readings, total cholesterol (TC) levels and cardiovascular risk (CVR) in patients with hypertension and/or hypercholesterolemia, at community pharmacies in Spain. The study was carried out in 18 community pharmacies in Spain with 6 months of PFU. Measurements were taken at: start, 6, 12, and 24 weeks. Hypertensive patients aged 35-74 attended with a prescription for at least one drug indicated primarily for the treatment of hypertension were included. A total of 117 patients completed the study. There were statistically significant increases in the achievement of hypertension targets (23.9%, p < 0.001). There were decreases in the average Wilson-Grundy CVR (-1.5%), CVR SCORE (-0.5%), systolic and diastolic BP (-7.6 mm Hg) (-3.3 mm Hg) and TC (-14.6 mg/dL). PFU carried out by community pharmacists in hypertensive patients attending community pharmacies in Spain improves BP, TC and can achieve BP, TC and CVR reduction.